A Personal History of Nuclear Medicine - Wagner, Henry N. (Springer London : Imprint: Springer, 2006)
In A Personal History of Nuclear Medicine, Dr. Henry N. Wagner, Jr. outlines his significant contribution to the field of nuclear medicine over the past half-century, while also discussing the hurdles that the field faced in becoming a major component of modern medical practice. Further, the author explores challenges within the academic and medical establishments, which have often been known for resisting change Written for nuclear medicine professionals and non-nuclear medicine professionals alike, A Personal History of Nuclear Medicine chronicles, from the point of view of a notable pioneer in the field, the challenges and problems faced during the development of nuclear medicine and its basic philosophy over the past half century, plus its further development within medicine as it moves into the future. Dr. Henry N. Wagner, Jr. is an international authority on nuclear medicine. His pioneering work in imaging brain neuroreceptors paved the way for groundbreaking research in addiction and drug design, and increased understanding of the physiology and pathophysiology of the brain. During his 56-year association with The Johns Hopkins University, he has trained more than 500 radiologists, internists, physicians, and scientists, eight of whom have held, as he has, the position of President of the Society of Nuclear Medicine. In 1985 he was awarded the Georg Von Hevesy Award and in 1993 Dr. Wagner was awarded the first Annual Society of Nuclear Medicine President's Award for Outstanding Contributions to nuclear medicine.